FusionWare Integration Server build composite applications quickly and easily. - Barbash, Brian (SOA webservices journal.)
In a service-oriented architecture, the ultimate goal is to quickly and easily build new applications as composites of existing services. Building out the independent services in a manner that supports reuse is itself very challenging. However, several tools are beginning to appear to easily bring applications together once the critical mass of applications is achieved. One such tool is the FusionWare Integration Server.